PENGARUH MAKANAN CEPAT SAJI TERHADAP KONSENTRASI BELAJAR - Aulia, Zabrina; Adiatmika, I Putu Gede; Tirtayasa, Ketut; Purnawati, Susy (E-Jurnal Medika Udayana, 2022)
The trend of changing eating patterns in today's adolescents cannot be separated from the influence of increasing socio-economic conditions and the number of interesting restaurants. With an unbalanced diet, eating fast food on a regular basis allows teens to develop anemia. Adolescents who suffer from anemia can experience growth disorders, decreased learning concentration, and lack of enthusiasm in carrying out activities because they feel tired quickly. This study aims to determine the effect of fast food on learning concentration in adolescents who regularly consume fast food. This study was an observational analytic study using a cross-sectional method and involved 106 samples. Based on the bivariate analysis using Chi-square correlation that has been carried out on the two variables, the interpretation of the final result of this study is that the frequency of fast food consumption per week has no correlation on learning concentration. This is because the analysis results obtained show a significant value between the frequency of consumption of fast food per week with a learning concentration of 0.875 and the odd ratio shows a value of 0.939. In this study, there is no effect of fast food on learning concentration in adolescents who regularly consume fast food. Keywords: fast food, learning concentration, anemia, correlation